Macroeconomics and consumption - Muellbauer, J (University of Oxford, 2016)
The failure of the ubiquitous New Keynesian "Dynamic Stochastic General Equilibrium" (NK-DSGE) models to capture interactions of finance and the real economy is widely-recognized since the 2008-9 financial crisis. NK-DSGE models exclude money, debt and asset prices and, importantly, ignore changing credit markets. These problems stem from assuming unrealistic micro-foundations for household behaviour, and that aggregate behaviour mimics a fully-informed representative agent (both assumptions are embodied in the underlying rational expectations permanent income' hypothesis (REPIH). This survey critiques the NK-DSGE models and its integral REPIH model, and discusses alternative post-crisis general equilibrium models which do incorporate debt and allow crises to occur. But neither model type can be directly applied to policy-making. The survey reviews misspecifications in standard non-DSGE macro-models used by central banks (e.g. the Fed.'s FRB-US), and related co-integration literature linking consumption with household portfolios. These too omit most of the 'financial accelerator', ignoring credit shifts and crucially, aggregating liquid, illiquid assets, debt and housing into a single 'net worth' construct. The survey's second focus is to improve non-DSGE models for policy using the Latent Interactive Variable Equation System (LIVES) approach, in which aggregate consumption is jointly modelled with the main elements of household balance sheets, extracting credit conditions as a latent variable. Empirical work on aggregate data is surveyed revealing the important role of debt and financial assets and the time and context-dependent role of housing collateral. Rather than 'one-size-fits-all' monetary and macro-prudential policy, institutional differences between countries then imply major differences for monetary policy transmission and policy.